Chemical Confinement and Utility of Lithium Polysulfides in Lithium Sulfur Batteries. Issue 6 (8th April 2019) - Tang, Tianyu; Hou, Yanglong
Abstract: Lithium sulfur (Li–S) batteries featuring abundant resources and cost‐efficiency are regarded as a promising next‐generation energy storage system with high theoretical capacity and energy density. However, several drawbacks impede the development of Li–S batteries, especially the shuttle effects of soluble lithium polysulfides (LiPS) which lead to severe capacity decay and short cycling lifespan. Though the existence of LiPS can result in performance decline and battery failure, the management of the LiPS should be balanced. This review focuses on both sides of the LiPS. One is the confinement of LiPS by chemical interactions between novel cathode hosts with LiPS, another is the utility of the LiPS in Li–S batteries with stable performance. Ultimately, the future developments and prospects of Li–S batteries are discussed. Abstract : Understanding the function of polysulfides is crucial to design Li–S batteries with reasonable configuration achieving wide application. Either disadvantages or advantages of lithium polysulfides (LiPS) cannot be ignored and the management of the LiPS should be balanced. Considering the chemical confinement and utility of LiPS is beneficial to deliver novel Li–S batteries satisfying future requirements.